2021
DOI: 10.1097/md.0000000000024702
|View full text |Cite
|
Sign up to set email alerts
|

Posterior interosseous nerve syndrome caused by a ganglion cyst and its surgical release with intraoperative neurophysiological monitoring

Abstract: Rationale: Intraoperative neurophysiological monitoring (IONM) has been utilized not only for the rapid detection of neural insults during surgeries, but also to verify the neurophysiological integrity of nerve lesions in the surgical field. Patient concerns: A 32-year-old woman presented with a wrist and finger drop that had lasted about 3 months. Diagnoses: The result of the initial electrodiagnostic test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Another useful tool besides ultrasonography for diagnosing neuropathy is electromyography, which helps localize the lesion and rule out brachial plexus injury [3] . The manifestation of PINs on electromyography is a reduced or blockage of motor nerve conduction at the injured site, a decrease in the response amplitude of the extensor digitorum muscle, and in addition, spontaneous potentials may appear in the extensor digitorum muscle; sensory conduction is still preserved [3 , 14] . In cases of PINs, anatomical variations that cause nerve compression are often difficult to visualize by MRI, however, MRI is sensitive in detecting muscle edema, muscle atrophy, and fatty infiltration [4] .…”
Section: Discussionmentioning
confidence: 99%
“…Another useful tool besides ultrasonography for diagnosing neuropathy is electromyography, which helps localize the lesion and rule out brachial plexus injury [3] . The manifestation of PINs on electromyography is a reduced or blockage of motor nerve conduction at the injured site, a decrease in the response amplitude of the extensor digitorum muscle, and in addition, spontaneous potentials may appear in the extensor digitorum muscle; sensory conduction is still preserved [3 , 14] . In cases of PINs, anatomical variations that cause nerve compression are often difficult to visualize by MRI, however, MRI is sensitive in detecting muscle edema, muscle atrophy, and fatty infiltration [4] .…”
Section: Discussionmentioning
confidence: 99%
“…Kravtsov et al [ 10 ] reported a case of neurinoma of the fifth lumbar nerve root that was surgically removed using endoscopy along with IONM; although motor weakness of the great toe extensor persisted, the patient’s pain of the L5 dermatome, which was present prior to the surgery, improved from a visual analog scale score of 7 to 2. In another case involving the surgical release of a ganglion cyst that was compressing the posterior interosseous nerve, resulting in symptoms of wrist and finger drop before the surgery, which was performed under IONM [ 11 ] ; partial recovery of wrist and finger extensor power was observed after the surgery. Patel et al [ 12 ] demonstrated that IONM could minimize the minor and major neural injuries during revision shoulder arthroplasty surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…Although IONM is good for monitoring underlying nerve damage, the efficacy of IONM-induced potential changes has been inconsistent. For example, SEP has been shown to be effective in monitoring spinal cord function during cervical and thoracic spine surgery, but not for nerve root levels during lumbosacral surgery [ 13 ]. SEP can also be used to evaluate specific nerve roots, but it cannot detect immediate changes in iatrogenic injury.…”
Section: Discussionmentioning
confidence: 99%